2009
DOI: 10.17221/1668-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Congenital disorders in the cattle population of the Czech Republic

Abstract: ABSTRACT:The aim of the paper was to analyse congenital disorders in the Czech cattle population in 1986-2001. The offspring of 474 sires -215 Czech Simmental, 236 Holstein, and 23 beef -were diagnosed with congenital disorders which were unevenly distributed because only 18 occurred in the progeny of 10 and more sires, in contrast to 88 occurring in the progeny of 1 sire only. Umbilical hernia was the most frequently noted disorder, and 136 sires fathered progeny with limb anomalies. The most frequent gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“…Os DCs podem ser hereditários ou terem causas infecciosas ou ambientais, ou ocorrerem por uma interação de ambos, agindo em um ou mais estágios do desenvolvimento fetal (Leipold & Dennis 1986, Cítek et al 2009). A ocorrência de casos de DCs com aumento gradual no nú-mero de animais afetados, associado ao uso contínuo dos mesmos reprodutores em rebanho de uma única origem está relacionada à doença hereditária por genes recessivos.…”
Section: Introductionunclassified
“…Os DCs podem ser hereditários ou terem causas infecciosas ou ambientais, ou ocorrerem por uma interação de ambos, agindo em um ou mais estágios do desenvolvimento fetal (Leipold & Dennis 1986, Cítek et al 2009). A ocorrência de casos de DCs com aumento gradual no nú-mero de animais afetados, associado ao uso contínuo dos mesmos reprodutores em rebanho de uma única origem está relacionada à doença hereditária por genes recessivos.…”
Section: Introductionunclassified
“…In this species, the CDC73 gene is assumed to be responsible for the malformation [ 36 ]. In cattle this condition is the most frequently noted congenital disorder [ 37 ] and it seems to be associated with genes located at the centromeric end of BTA8 [ 38 ]. Additionally, this is the most common malformation in river buffalo, but only a few cases are well described in the literature, like in the Pandharpuri buffalo breed in which Amle et al [ 39 ] found a male calf with incomplete closure of umbilicus and reducible intestinal hernia associated to cryptorchidism, and in MIRB, in which Correale and Consalvo [ 9 ] found 72 cases with different phenotypic traits.…”
Section: Musculoskeletal Defectsmentioning
confidence: 99%
“…Dicephaly (dicephalus; two-headed monster) is a peculiar type of conjoined twins observed in cattle (Cornillie et al 2006;Čítek et al 2009). The case of a two-headed bull shark described by Wagner et al (2013) proves that this malformation has a universal character in vertebrates.…”
Section: Brain Base Arteries Head Vascularity Ruminantmentioning
confidence: 99%